Potensi Internet of Things (IoT) sebagai Sumber Official Statistics Bidang Pertanian - Ramadani, Resi (Seminar Nasional Official Statistics, 2023)
Significant technological developments have had a major impact on various aspects of life, including data collection and processing. With the presence of technology that produces Big Data and the Internet of Things (IoT), data can be obtained in real time at a relatively low cost. IoT as a source of Big Data has the ability to collect various data, such as text, images, video and sound automatically and continuously. In the context of agricultural statistics, the application of IoT and Big Data has significant potential. Accurate and real time data collection and analysis is critical to optimizing agricultural production, increasing efficiency, and meeting the challenge of climate change. This research will examine how the opportunities and challenges of IoT as a source of official statistics carry out a literature review. Based on the existing literature, it can be concluded that the use of IoT in agricultural statistics can provide great benefits, but care must be taken to maintain the integrity and credibility of official statistics data.